The Relationship Between Academic Motivation and Lifelong Learning During Residency: A Study of Psychiatry Residents. (October 2016) - Sockalingam, Sanjeev; Wiljer, David; Yufe, Shira; Knox, Matthew K.; Fefergrad, Mark; Silver, Ivan; Harris, Ilene; Tekian, Ara
Abstract : Purpose: To examine the relationship between lifelong learning (LLL) and academic motivation for residents in a psychiatry residency program, trainee factors that influence LLL, and psychiatry residents' LLL practices. Method: Between December 2014 and February 2015, 105 of 173 (61%) eligible psychiatry residents from the Department of Psychiatry, University of Toronto, completed a questionnaire with three study instruments: an LLL needs assessment survey, the Jefferson Scale of Physician Lifelong Learning (JeffSPLL), and the Academic Motivation Scale (AMS). The AMS included a relative autonomy motivation score (AMS-RAM) measuring the overall level of intrinsic motivation (IM). Results: A significant correlation was observed between JeffSPLL and AMS-RAM scores ( r = 0.39, P < .001). Although there was no significant difference in JeffSPLL and AMS-RAM scores based on respondents' level of training (senior vs. junior resident), gender, or age, analysis of AMS subdomains showed that junior residents had a significantly higher score on the extrinsic motivation identification domain (mean difference [M] = 0.38; 95% confidence interval [CI] [0.01, 0.75]; P = .045; d = 0.44) compared with senior residents. Clinician scientist stream (CSS) residents had significantly higher JeffSPLL scores compared with non-CSS residents (M = 3.15; 95% CI [0.52, 5.78]; P = .020; d = 0.57). Conclusions: The use of rigorous measures to study LLL and academic motivation confirmed prior research documenting the positive association between IM and LLL. The results suggest that postgraduate curricula aimed at enhancing IM, for example, through support for learning autonomously, could be beneficial to cultivating LLL in learners.